Belly up - Gibbs, Stuart, 1969- (New York : Scholastic, 2010)
Twelve-year-old Teddy investigates when a popular Texas zoo's star attraction, Henry the Hippo, dies from not-so-natural causes.
5.6.
5-8.
820L
W
Keywords: Mystery and detective stories; Hippopotamus -- Fiction; Zoos -- Fiction; Zoo animals -- Fiction